Cardiovascular Adverse Event Risk in Rheumatoid Arthritis Patients Treated with JAK Inhibitor Tofacitinib versus TNF Inhibitors: a Systematic Review, Meta Analysis, and Meta Regression - Kynaya, Erlangga Masykur; Salfistra, Nadia Ramadhina; Hanun, Jauza' 'Athifah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Rheumatoid arthritis (RA) is a chronic autoimmune disease, often requiring potent therapies like Tofacitinib or TNF inhibitors. Yet the comparative cardiovascular safety profile of these agents remains a critical and evolving concern. Previous meta-analysis revealed major adverse cardiovascular events (MACE) and thromboembolism was prevalent in tofacitinib treated patients. However, the impact of patient comorbidities on cardiovascular adverse events remains uncertain, requiring systematic assessment through meta-analysis and meta-regression. This study aims to assess the risk of cardiovascular adverse events in RA patients treated with tofacitinib versus TNF inhibitors and to evaluate the influence of baseline comorbidities through meta-regression. A comprehensive search of PubMed, Scopus, Scilit, and Epistemonikos identified RCTs and observational studies up to 2025. Random-effects meta-analysis in R estimated pooled OR and HR for MACE and thromboembolism, while patient comorbidities were evaluated through meta-regression. Four studies (n = 62,009) met inclusion criteria. Tofacitinib was associated with increased risk of MACE (HR = 1.33; 95% CI 1.08–1.65; p = 0.008; I² = 0%) and thromboembolism (HR = 1.79; 95% CI 1.23–2.60; p = 0.002; I² = 37.8%) compared with TNF inhibitors. Meta-regression revealed no significant effect of age, sex, hypertension, diabetes, smoking, heart failure, coronary artery disease, venous thromboembolism history, or corticosteroid use on these risks. Tofacitinib increases the risk of MACE and thromboembolism in RA patients compared with TNF inhibitors, independent of common cardiovascular comorbidities and baseline characteristics.